Halal Tourism Based on Local Culture: Maqāṣid Al-Syarī'Ah Analysis of the Views of Yogyakarta Scholars - Masruroh Masruroh; Zulkifli Zulkifli; Masri Mansoer; Arif Zamhari (Universitas Muhammadiyah Bandung, 2025)
Halal tourism has increasingly developed as a strategic sector within the Islamic economy, particularly in culturally rich destinations such as Yogyakarta. However, previous studies have largely focused on marketing, Muslim tourist behavior, certification, policy, and destination competitiveness. Limited attention has been given to the normative construction of religious scholars’ views on the integration of local culture into halal tourism. This study aims to analyze the perspectives of Yogyakarta religious scholars on the relationship between halal tourism and local culture and to examine them from the perspective of sharia economic law. This research employs qualitative field research with a case study design, combined with normative sharia economic law analysis. Primary data were obtained through guided interviews with eight religious scholars representing Nahdlatul Ulama, Muhammadiyah, Salafi, the Indonesian Ulema Council, pesantren, female scholars, academics, and Muslim cultural figures. The data were analyzed using the Miles and Huberman model and validated through source and theoretical triangulation. The findings show that Yogyakarta religious scholars view halal tourism not as a formalization of Islamic symbols, but as the internalization of sharia values into tourism practices while respecting local culture. Their differing views reflect accommodative, moderate, selective, and contextual patterns. Theoretically, this study contributes to the development of sharia economic law scholarship by offering an integrative analysis of maqāṣid al-sharī‘ah, ‘urf, maslahah, and sadd al-dzarī‘ah in legitimizing local culture within halal tourism.